2023
DOI: 10.1038/s41598-023-28902-8
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring storm evolution using a high-density seismic network

Abstract: Data acquired by a dense seismic network deployed in the Cerdanya basin (Eastern Pyrenees) is used to track the temporal and spatial evolution of meteorological events such as rainfall episodes or thunderstorms. Comparing seismic and meteorological data, we show that for frequencies above 40 Hz, the dominant source of seismic noise is rainfall and hence the amplitude of the seismic data can be used as a proxy of rainfall. The interstation distance of 1.5 km provides an unprecedented spatial resolution of the e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Diaz et al [195] showed that at frequencies above 40 Hz, most seismic signals at their field site in Spain were generated by rainfall. This then suggested that frequencies above this threshold could be used to monitor rainfall.…”
Section: Seismic Methods For Recording Rainfallmentioning
confidence: 99%
“…Diaz et al [195] showed that at frequencies above 40 Hz, most seismic signals at their field site in Spain were generated by rainfall. This then suggested that frequencies above this threshold could be used to monitor rainfall.…”
Section: Seismic Methods For Recording Rainfallmentioning
confidence: 99%
“…distinguishing precipitation types such as snow or rain) or radar bright-band detection, which facilitates the data analysis (more information and public access to this post-processing software can be found in [15,17,19]). Classification of the precipitation type is an essential aspect here as it allows to separate liquid from solid precipitation, given that erosivity of rainfall is computed from particle size distributions identified as rain drops, from which kinetic energy is calculated given their terminal velocity [20,11,21]. Moreover, the application of RaProM-Pro also allows to provide the frequency of occurrence of different precipitation types, which is also relevant to study the impact of precipitation on wind turbines.…”
Section: Mrr Data Postprocessingmentioning
confidence: 99%
“…Several researchers have carried out different seismological analyses of SBN to characterize cyclone generated oceanic as well as seismic waves for their effective monitoring (e.g., Borzi et al., 2022; Chi et al, 2010; Diaz et al, 2023; Fan et al., 2019; Gerstoft et al., 2006; Gualteri et al, 2018; Hua et al, 2023; Retailleau & Gualtieri, 2019; Sufri et al, 2014; Tabulevich, 1971; Zhang et al, 2010). They applied a wide range of methods to monitor oceanic storms with seismological waveforms, such as single station (Sufri et al., 2014), array analysis (Borzi et al., 2022; Hua et al, 2023), and seismic interferometry (Retailleau et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The ambient seismic ground vibration, also called seismic background noise (SBN) of the solid earth is originated mainly due to oceanic‐driven winds such as tropical cyclones, extratropical cyclones, and other stormy phenomena (e.g., Brwomirski, 2001; Chi et al., 2010; Díaz et al., 2023; Gualtieri al., 2018; Hua et al., 2023; Retailleau & Gualtieri, 2021; Schulte‐Pelkum et al., 2004; Webb, 1992) and it can be recorded globally using seismographs. The accepted mechanisms responsible for the generation of SBNs are (a) direct coupling between oceanic waves in shallower water and that near the seafloor in the 10–20 s period (Webb, 2002) and (b) nonlinear interaction of two sets of opposite moving oceanic gravity waves having similar frequency content that generate <10 s microseism (Ekström & Ekström, 2005; Longuet‐Higgins, 1950; Rhie & Romanowicz, 2004).…”
Section: Introductionmentioning
confidence: 99%